Penerapan Algoritma Simple Additive Weighting (SAW) pada Sistem Informasi Penjualan Berbasis Web di Konter Servis Handphone - Siti Musabiah Mega Pratiwi; Rasim; Setiawati, Siti (Journal of Informatic and Information Security, 2022)
Thomas Cell is a business outlet that provides cellphone service, and sells cellphone accessories. The purpose of research conducted by researchers at Thomas Cell is to design an information system to process service data and check accessories according to consumer budgets. The old system adapts to various types of changes in its environment, to the point where the system can no longer adapt to the problems in its environment. Then a new system was created to replace it. The technique used to design this application is the System Development Life Cycle (SDLC) technique, this technique suggests an approach to structuredsoftware development, starting from the stages and progress of the system for all analysis, design, code, testing, and maintenance. In designing software and compiling reports on this system, it is designed on a website basis. This information system can reduce errors that occur in managing service data, later checking service data can be carried out quickly, easily, effectively, efficiently, and the data obtained can be more accurate and it can also be easier to have conversations about data, so there is no need to meet each other.